Nyamnjoh, Francis B, #RhodesMustFall: Nibbling at Resilient Colonialism in South Africa. Langaa Research and Publishing Common Initiative Group 2016, 298 pp. (The Strategic Review for Southern Africa, 2020)
Nyamnjoh's #RhodesMustFall is a timely release that unapologetically incorporates through a critical discourse analysis, the nuances and debates buried in the mainstream analysis of the various Fallist Movements. Nyamnjoh follows pertinent narratives about the #RhodesMustFall protests and of the need to re-evaluate transformation beyond the obsession of symbols (pp 84-85). The protests are about "revolting against the terms of engagement dictated to them" (p 84) and about deep seated frustrationswith the nature, extent and type of transformation that had been taking place (p157).
Keywords: police violence; #RhodesMustFall; colonialism; decolonisation; colonial education